High surface area nanoporous carbon derived from high quality jute from Bangladesh - Khan, Junayet Hossain; Lin, Jianjian; Young, Christine; Matsagar, Babasaheb M.; Wu, Kevin C. W.; Dhepe, Paresh L.; Islam, Md Tofazzal; Rahman, Md Mahbubur; Shrestha, Lok Kumar; Alshehri, Saad M.; Ahamad, Tansir; Salunkhe, Rahul R.; et al. (Materials Chemistry and Physics, 2018)
We report an economically viable and environment-friendly strategy for the preparation of nanoporous carbon (NC) from jute which is one of the most abundant natural fibers produced in Bangladesh and some South Asian countries. Nitrogen adsorption-desorption isotherms, X-ray diffraction, Raman spectroscopy, UV spectroscopy, and scanning/transmission electron microscopy were performed to characterize the obtained NC. Three different types of jute-derived NCs have been synthesized at three different temperatures, 700 degrees C, 800 degrees C and 900 degrees C. The NC prepared at 800 degrees C resulted in a high surface area (981 m(2) g(-2)) and was associated with the retention of the original fibrous shapes. This study shows a promising future for jute as a natural precursor for NCs for a myriad of applications ranging from water purification to gas separation to energy conversion and storage.
Keywords: Adsorbents; Graphitization; Jute; Nanoporous carbons; porous materials